Habiter sur serre à Eden Square. Un espace collectif tempéré à l’épreuve de ses habitants - Valérie Foucher-Dufoix; Laetitia Overney (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
This paper reports on a bioclimatic building of 87 housing units organized around a green house, Eden Square, delivered in 2012 in the Rennes urban area (France) by architects Christian Hauvette and Pierre Champenois, who describe it as “a social and ecological utopia”. Living in a greenhouse would seem to be an unusual experience. But how do the inhabitants really live and perceive Eden Square? What about the pleasure of living in a greenhouse? Are we dealing with an Eden, by definition decontextualized, and a hyper-conditioned space? The article is based on a sociological survey carried out between 2017 and 2019 among the inhabitants of the building. It shows how the pleasure of living in these spaces is above all due to the sensory experience, the pleasure of the route, the comfort of the homes, the thermal performances, without generating any particular collective life. Eden Square is not experienced by these inhabitants as a “world-building”, self-centred on the greenhouse as an autonomous social entity without having any connection with the outside world. Nevertheless, the greenhouse remains a space to be contemplated without any real possibility of appropriation.